An analysis of conference attendees’ motivations: Case of international conference attendees in Singapore - Malek, Anahita (2015)
This research intends to capture the underlying motivations for the decision of conference attendees to participate in an international conference. This study also aims to investigate if motivational differences exist among attendees with different gender, age, and nationality. Data were collected through a survey, target specific information about the motivational attitudes of conference attendees. The findings revealed that there are four dimensions of conference motivations: professional and prestige, pleasure seeking, destination factors, and conference factors. The results also showed that the relationship between demographic characteristics and the motivational attitudes are statistically not significant.